Cash Waqf Linked Sukuk model for export micro, small, and medium enterprises financing affected by Covid-19 pandemic: Indonesian study - Siswantoro, Siswantoro (Asian Management and Business Review, 2022)
The purpose of this research is to solve the problem of financing export-oriented MSMEs affected by the Covid-19 pandemic, by exploring and building Cash Waqf Linked Sukuk (CWLS) model. The research method used is qualitative. The data sources used are of the secondary type in the form of journal articles, books, reports from the government, national news websites, and other relevant sources that have previously been accessed and downloaded. The data analysis technique uses descriptive analysis, by analyzing the reference sources that have been collected and then integrated with the research argument. The results show that CWLS model has the potential to be an alternative source of new funding that is safe, easy, and risk-free for export-oriented MSMEs actors affected by the pandemic. Other findings show that the potential for cash waqf that can be explored in Indonesia reaches IDR. 13.9 trillion per year, so it has the opportunity to finance as many as 27,800 new export-oriented MSMEs. In addition, the value of the use of waqf funds is quite large, reaching IDR. 1.3 trillion with a two-year tenor. This value is sufficient to finance social development projects such as mosques or schools.